Colossal increase in negative magnetization, exchange bias and coercivity in samarium chromite due to a strong coupling between Sm3+-Cr3+ spins sublattices - Gupta, Preeti; Bhargava, Richa; Poddar, Pankaj (Journal of Physics D-Applied Physics, 2015)
We report giant temperature dependent negative magnetization (magnetization reversal) along with a large exchange bias and large coercivity in SmCrO3. The static magnetization measurements show the negative magnetization below similar to 192 K, due to competition between the external field, thermal activation energy and antiparallel Sm3+-Cr3+ spin interaction. At further lower temperatures, Sm3+ spins show an increased alignment due to the internal induced field of Cr3+ spins with minimum magnetization similar to - 0.037 emu g(-1). The temperature dependent exchange bias shows non-monotonic behavior. At 35 K, the exchange bias ceases to exist due to the orientation of Sm3+ moments with respect to canted Cr3+ moments. The crossover temperature decreases from similar to 191 K at 100 Oe to similar to 153 K at 250 Oe. The training effect further confirms the exchange bias in SmCrO3. The dynamic magnetization measurements exhibit anomalies around spin reorientation transition (T-SR similar to 34 K) and Neel transition (T-N similar to 192 K) which is consistent with static measurement and no frequency dependence was observed. The room temperature Raman spectra of SmCrO3 show peaks at similar to 364, similar to 375 and similar to 456 cm(-1) suggesting O-Cr-O bending modes within the octahedral.
Keywords: exchange bias; multiferroics etc; negative magnetization; samarium chromite; spin reorientation